Coordinated control strategy for the common-rail pressure using a metering unit and a pressure control valve in diesel engines. (June 2015) - Hong, Seungwoo; Shin, Jaewook; Sohn, Jeongwon; Park, Inseok; Sunwoo, Myoungho
Since the fuel injection pressure in diesel engines is one of the main parameters which determine the emissions and the fuel efficiency, a precise control algorithm for the common-rail pressure is a required priority for improving the engine performances. This paper proposes a coordinated common-rail pressure control strategy for passenger car diesel engines using a metering unit and a pressure control valve. The metering unit, which is located at the high-pressure pump, adjusts the inlet fuel flow for the common rail using a first-order polynomial equation that describes the relation between the inlet fuel flow and the outlet fuel flow for the common rail. The injected fuel flow is used as the input for the control algorithm to determine the driving current of the metering unit. The designed control strategy for the metering unit effectively reduces the rail pressure wave generated by the high-pressure pump. Furthermore, since the inlet fuel flow is adjusted according to the injected fuel flow, the proposed control algorithm shows a robust performance to the injection disturbance. The pressure control valve located on the common rail adjusts the outlet fuel flow of the common rail. The control algorithm for the pressure control valve is designed using quantitative feedback theory to assure robustness even when the variation in the plant characteristics (such as the static gain and the time constant) is caused by the metering unit operation. Engine experiments proved that the proposed control strategy can reduce the variation in the steady-state rail pressure to less than 10 bar; in addition, the proposed rail pressure controller has a good degree of consistency under various engine operating conditions.